Bio-stimulatory effects of bull urine (BU), PRID and GnRH on hormonal profile and association with blood minerals in pubertal anestrus Sahiwal heifers - AHMED, ABRAR; TIWARI, R P; KHAN, J R; TIWARI, S P; MISHRA, G K (The Indian Journal of Animal Sciences, 2017)
The present study was designed to assess the bio-stimulatory effect of bull urine (BU) exposure, administrationof progesterone impregnated intravaginal device (PRID) in combination with PGF2α and gonadotropin releasinghormone (PRID-PG-GnRH), and GnRH in combination with PGF2α (GnRH-PG-GnRH) on alteration of hormonalprofile in correlation with induction of estrus in pubertal anestrus Sahiwal heifers. Pubertal anestrus Sahiwal heifers(32) were randomly divided into 4 groups, viz. group 1 (8; BU), group 2 (8; PRID-PG-GnRH), group 3 (8; GnRHPG-GnRH) and group 4 (8; Control). Treatment with PRID-PG-GnRH and GnRH-PG-GnRH significantly increased the serum progesterone and estrogen concentration whereas, in BU and untreated control heifers, the progesteroneconcentration remained at the basal level during 30 days observation period. However, a meager increase of serumestrogen concentration was observed from day 9 and 11 in BU treated heifers. The association of certain macro andmicro minerals level in blood during pre and post treatment period was studied to correlate the treatment response. Significant difference was observed in mean serum calcium (mg/dl) and iron (ppm) levels in pre and post BU exposed, PRID-PG-GnRH and GnRH-PG-GnRH treated heifers compared to the control. No significant differencein mean serum phosphorus (mg/dl), copper (ppm) and cobalt (ppm) level was observed in all the groups. Significantdifference was observed in mean serum magnesium (mg/dl) and zinc levels in pre and post PRID-PG-GnRH andGnRH-PG-GnRH treated heifers as compared to BU exposed and control heifers. Thus, it can be concluded that thetreatment with PRID-PG-GnRH and GnRH-PG-GnRH had more pronounced effect on induction of estrus as reflectedby increased level of serum estradiol on day 9 and progesterone level on 10th day post AI than the bull urine treatedand control heifers and subsequent increase in serum calcium, magnesium, iron, and zinc levels during post treatment period in pubertal anestrus Sahiwal heifers.